DETERMINATION OF ANTIMICROBIAL EFFECT, ANTIOXIDANT ACTIVITY AND PHENOLIC CONTENTS OF DESERT TRUFFLE IN TURKEY - DoÄŸan, Hasan HÃ¼seyin; AydÄ±n, Sema (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Terfezia boudieri Chatin (Scop.) Pers., is a famous macrofungus in the world as well as in Turkey for its pleasant aroma and flavour. People believe that this mushroom has some medicinal properties. Therefore, it is consumed as food and for medicinal purposes. Chloroform, acetone and methanol extracts of T. boudieri were tested to reveal its antimicrobial activity against four Gram-positive and five Gram-negative bacteria, and one yeast using a micro dilution method. In this study, the highest minimum inhibitory concentration (MIC) value was observed with the acetone extract (MIC, 4.8 µg/mL) against Candida albicans. Maximum antimicrobial effect was also determined with the acetone extract (MIC, 39-78 µg/mL). The scavenging effect of T. boudieri on 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radicals was measured as 0.031 mg/mL at 5 mg/mL concentration, and its reducing power was 0.214 mg/mL at 0.4 mg/mL. In addition, the phenolic contents were determined as follows: the catechin was 20 mg/g, the ferulic acid was 15 mg/g, the p-coumaric acid was 10 mg/g, and the cinnamic acid was 6 mg/g. The results showed that T. boudieri has antimicrobial activity on the gram negative and positive bacteria as well as yeast, and it also has a high antioxidant capacity. Therefore, T. boudieri can be recommended as an important natural food source.